2019
DOI: 10.1080/2162402x.2018.1558678
|View full text |Cite
|
Sign up to set email alerts
|

Order of administration of combination cytokine therapies can decouple toxicity from efficacy in syngeneic mouse tumor models

Abstract: 2019) Order of administration of combination cytokine therapies can decouple toxicity from efficacy in syngeneic mouse tumor models, OncoImmunology, 8:5, e1558678, ABSTRACTIn combination cancer immunotherapies, consideration should be given to designing treatment schedules that harmonize with the immune system's natural timing. An efficacious temporally programmed combination therapy of extended half-life interleukin 2 (eIL2), tumor targeting antibody, and interferon (IFN) α was recently reported; however, tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…In stark contrast, no mice were cured when MSA-IL2 was combined with IFNα, MSA-IFNα, or IFNβ. However, we and others have observed that cytokine combinations can exacerbate treatment-related toxicities (21,54,55). Extended half-life MSA-IFNα combined with MSA-IL2 led to substantial weight loss, and four out of seven mice were killed due to toxicity (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In stark contrast, no mice were cured when MSA-IL2 was combined with IFNα, MSA-IFNα, or IFNβ. However, we and others have observed that cytokine combinations can exacerbate treatment-related toxicities (21,54,55). Extended half-life MSA-IFNα combined with MSA-IL2 led to substantial weight loss, and four out of seven mice were killed due to toxicity (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Preclinical research suggests that antiangiogenic agents could exert a priming of the immune microenvironment [12-15, 17-19, 30]. Particularly, the sequence in which these agents are administered (sequential versus concurrently with immunotherapy) might be of key importance [25,26]. The efficacy assessment and the correlative studies results deserve attention.…”
Section: Discussionmentioning
confidence: 99%
“…The efforts invested in studying immune-boosting combinations, however, have paid little attention to the timing of administration of the "immune enhancer". The natural rhythms of innate and adaptive response could be used to enhance the efficacy of anti-PD-1/PD-L1 agents by combining them with agents in the right sequence [25,26]. In that sense, it is possible that pre-treatment with a VEGF-A inhibitor could exert an immuno-priming effect that would increase the chance of response to subsequent immune checkpoint blockade and be more effective than concurrent therapy [26], while causing less adverse events [12].…”
Section: Introductionmentioning
confidence: 99%
“…One theory is that multiple redundant immunosuppressive pathways must be targeted in the tumor and that combination approaches could sufficiently disable these layered defenses to illicit a potent antitumor immune response. , Combinatorial immunotherapy is challenging in several ways, with the most notable perhaps being significant increases in toxicity seen in clinical trials . Combining immunomodulating agents is also complicated by schedule-dependent effects that are only beginning to be understood but that have a clear and significant effect on both safety and efficacy. Initial studies into combination immunotherapy are also revealing that dosing strategies might not need to resemble the conventional approaches established by chemotherapy, such as multiple cycles of drug. For example, clinical trials that combined PD-1 and CTLA-4 checkpoint antibodies reported that patients who ultimately discontinued the trial due to toxicity saw similar benefits to patients who completed the trial. , These data provide a provocative basis to explore different dosing frequencies and strategies.…”
Section: Hydrogels For Drug Deliverymentioning
confidence: 99%